Darkening nights and rooftop solar adoption under South Africa’s electricity crisis: geographies of the energy apartheid - Zander S Venter; Shylet Chivanga; Megan Davies; Priscilla Monyai; Samantha L Scott (Environmental Research: Energy)
Solar energy is the fastest-growing renewable electricity source globally. Under the guise of the green transition, solar energy is portrayed by energy optimists as sustainable despite its negative environmental and social externalities. The justice and equity dynamics of solar energy adoption have not been adequately explored in the Global South, where there are fewer incentives to transition away from carbon-based energy. South Africa poses a unique exception where, under a national energy crisis, load shedding (i.e. rolling electricity outages) has led to an exponential increase in household solar adoption. In order to quantify energy justice dynamics, we manually mapped solar installations for a representative sample of 300 urban census tracts across South Africa. We found that while solar adoption increased at a rate of 140% per year between 2016 and 2023, it was unevenly distributed over socio-economic geographies, particularly when comparing white and previously disadvantaged population groups (Black African, Colored, and Indian). Household solar adoption was close to zero in census tracts with income levels just above or below the poverty line, whereas high-income tracts installed nearly 2 panels per household, on average. Similarly, solar adoption is 73 times higher in majority white census tracts compared to those with majority previously disadvantaged racial groups (average of 3.5 m ^2 vs 0.048 m ^2 panel area per person). Using satellites that measure nighttime light radiance, we found that solar panel adoption is associated with less severe nighttime light declines, suggesting solar increases household resilience to load shedding. Census tracts with majority Black African residents show declines in nighttime light that are twice as large as those in majority White tracts, thereby mirroring the solar adoption pattern. Our findings illustrate the extremes of energy injustice in the Global South where existing social asymmetries are perpetuated and amplified in the green energy transition.